“If it weren’t for my traditional healer, I would be dead”: Engaging traditional healers to support people living with HIV in rural Mozambique - Carolyn M Audet; Mariah Pettapiece-Phillips; Yuqi Tian; Bryan E Shepherd; Sten H Vermund; Jose Salato (My University, 2022)
Across rural sub-Saharan Africa, people living with HIV (PLHIV) commonly seek out treatment from traditional healers. We report on the clinical outcomes of a community health worker intervention adapted for traditional healers with insight into our results from qualitative interviews. We employed a pre-post intervention study design and used sequential mixed methods to assess the impact of a traditional healer support worker intervention in Zambézia province, Mozambique. After receiving a positive test result, 276 participants who were newly enrolled in HIV treatment and were interested in receiving home-based support from a traditional healer were recruited into the study. Those who enrolled from February 2016 to August 2016 received standard of care services, while those who enrolled from June 2017 to May 2018 received support from a traditional healer. We conducted interviews among healers and participants to gain insight into fidelity of study activities, barriers to support, and program improvement. Medication possession ratio at home (based on pharmacy pick-up dates) was not significantly different between pre- and post-intervention participants (0.80 in the pre-intervention group compared to 0.79 in the post-intervention group; p = 0.96). Participants reported receiving educational and psychosocial support from healers. Healers adapted their support protocol to initiate directly observed therapy among participants with poor adherence. Traditional healers can provide community-based psychosocial support, education, directly observed therapy, and disclosure assistance for PLHIV. Multiple factors may hinder patients' desire and ability to remain adherent to treatment, including poverty, confusion about medication side effects, and frustration with wait times at the health facility.